2022
DOI: 10.1111/omi.12402
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bdellovibrio bacteriovorus HD100 on experimental periodontitis in rats

Abstract: Aim The aim of this study was to evaluate the effects of Bdellovibrio bacteriovorus HD100 on experimental periodontitis (EP) in rats. Methods Thirty‐two rats were divided into four groups: control, C‐HD100 (B. bacteriovorus), EP, and EP‐HD100. On day 0, EP was induced by the placement of cotton ligatures around the mandibular first molars (MFMs) in the EP and EP‐HD100 groups. In the C‐HD100 and EP‐HD100 groups, suspensions containing 1 × 109 PUF/ml of B. bacteriovorus HD100 were topically administered to the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…It has been demonstrated that Bdellovibrio bacteriovorus are indifferent to the antibiotic-resistance status of their prey [6,7]. Moreover, it has been demonstrated that predatory bacteria are nontoxic to mammalian cells and in animal models and have the ability to attenuate Gram-negative bacteria in several in vivo models, including but not limited to airway and oral infections in rodents and central nervous system infection of zebrafish hindbrain ventricles [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that Bdellovibrio bacteriovorus are indifferent to the antibiotic-resistance status of their prey [6,7]. Moreover, it has been demonstrated that predatory bacteria are nontoxic to mammalian cells and in animal models and have the ability to attenuate Gram-negative bacteria in several in vivo models, including but not limited to airway and oral infections in rodents and central nervous system infection of zebrafish hindbrain ventricles [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that predatory bacteria are indifferent to the antibiotic-resistance status of their prey [6,7]. Moreover, it has been demonstrated that predatory bacteria are non-toxic to mammalian cells and in animal models and have the ability to attenuate Gram-negative bacteria several in vivo models, including but not limited to airway and oral infections in rodents and central nervous system infection of zebrafish hindbrain ventricles [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%